2020
DOI: 10.3390/met10060747
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization and Mechanical Properties of Fiber Laser Welded CP-Ti and Ti-6Al-4V Similar and Dissimilar Joints

Abstract: In this research, the microstructures and mechanical properties of similar and dissimilar autogenous joints of 3 mm thick commercially pure titanium (CP-Ti) and Ti-6Al-4V welded by ytterbium fiber laser (Yb:YAG) were investigated. Two sets of laser power and welding speed were selected in such a way that the heat input remained constant. Microstructural characterization of the joints was investigated by an optical microscope, and mechanical properties were determined by hardness and tensile tests. The only def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Tensile testing results highlighted that samples had sustained ductility in all directions measured through percent elongation and percent reduction in area, with average values of 8.9 ± 1.1% and 8.0 ± 1.2%, respectively, as presented in Table 2. This compares well with similar additive manufacturing processes involving commercially pure Ti [35,36], where a slight improvement in tensile strength is noted in this work with conserved ductility. Directionality of TiB particles can play a role in the strengthening effect of these additions within TMCs, where TiB behaves as discontinuous fibres within Ti alloys [15,34].…”
Section: Discussionsupporting
confidence: 86%
“…Tensile testing results highlighted that samples had sustained ductility in all directions measured through percent elongation and percent reduction in area, with average values of 8.9 ± 1.1% and 8.0 ± 1.2%, respectively, as presented in Table 2. This compares well with similar additive manufacturing processes involving commercially pure Ti [35,36], where a slight improvement in tensile strength is noted in this work with conserved ductility. Directionality of TiB particles can play a role in the strengthening effect of these additions within TMCs, where TiB behaves as discontinuous fibres within Ti alloys [15,34].…”
Section: Discussionsupporting
confidence: 86%
“…Metals and plastics are widely used in industrial applications, and the connection of a metal part with a plastic part is often necessary and important from a manufacturing point of view. Therefore, the combination of a metal material and a laser-assisted plastic material (LAMP) has been developed as an innovative direct laser joint, without adhesives or glue [1,2]. It has been demonstrated that the joining of metal and plastic materials through LAMP technology offers a high-strength nanostructural bonding through formation of an oxide film that has high reliability in various practical uses [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Elements of fundamental metallurgy and microstructural evolution are described for highly specialised titanium-based laser welded joints, shape memory alloys, additive manufactured parts and biomedical Ti-Ni alloys (Abdollahi et al [2], Huang et al [3], Panin et al [4], Cascadan and Grandini [5], respectively). Choe et al [6] describe grain boundary TiFe precipitation in a α + β alloy and the employment of isothermal aging as a mechanism for controlling subsequent strength.…”
mentioning
confidence: 99%